How lucky [compact disc, unabridged] - Leitch, Will (Harper Audio, 2021)
Daniel leads a rich life in the university town of Athens, Georgia. He's got a couple close friends, a steady paycheck working for a regional airline, and of course, for a few glorious days each Fall, college football tailgates. He considers himself to be a mostly lucky guy, despite the fact that he's suffered from a horrible illness since he was a small child, one that has left him unable to speak or to move without a wheelchair. Largely confined to his home, Daniel spends the hours he's not online communicating with irate air travelers observing his neighborhood from his front porch. One young woman passes by so frequently that spotting her out the window has almost become part of his daily routine. Until the day he's almost sure he sees her being kidnapped.